MOTIF KALAMAKARA PADA TEMUAN PERHIASAN EMAS ERA MAJAPAHIT KOLEKSI MUSEUM NASIONAL JAKARTA - Waridah Muthiah; Agus Sachari (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
Jewelry in the Classical era in Indonesia, especially in the Late Classic era, occupies an important position in society. Apart from being a symbol of a person's status and position, when discussing the depiction of jewelry on a statue or relief, the jewelry worn by a character is also an indication in determining the identity of the character. Jewelry in the Late Classical era was made of gold, which was considered to have high material, symbolic, and religious value in society at that time. Based on the findings of jewelry in the Late Classic era, especially the Majapahit era, there is an interesting phenomenon, namely the depiction of animal figures as decorations or ornaments. This phenomenon is seen in the crown, earrings, and shoulder harness, as found in Trowulan. In some jewelery, the form of kalamakara (kalamakara) is displayed, which is usually depicted on the gate of the temple, as a repellent to disaster. The depiction of kalamakara in jewelry raises questions about the background behind the depiction. This research was conducted using qualitative methods through observation of four samples of Majapahit era jewelry found in Trowulan, the collection of the Jakarta National Museum. It can be concluded that the existence of kalamakara as a motif in jewelry is related to the meaning of kalamakara in Javanese society, namely as a repellent for disaster. Keywords: jewelry, kalamakara motif, Majapahit era